The Impact Of Talent Management And Organisational Culture On Employee Retention In It Industry In India - Shanmugam, Senthilnathan (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation explores the intricate relationship between talent management practices and organizational culture in the context of employee retention within India's IT industry. The study aims to address the pressing challenge of retaining skilled professionals in a sector characterized by rapid technological advancements, intense competition, and high turnover rates. Talent management, encompassing strategies for attracting, developing, and retaining employees, is critical for organizational success. Equally important is organizational culture, which shapes the work environment and influences employee satisfaction and commitment. The research employs a quantitative approach, utilizing purposive sampling to gather data from IT professionals in Bangalore, Chennai, and Pune. 660 IT professionals selected as sample size for the existing study. The study investigates various talent management practices, including recruitment, training, performance management, career development, employee engagement, recognition, and succession planning. It also examines the impact of organizational culture on employee retention, focusing on aspects such as inclusiveness, work-life balance, leadership, and innovation. The findings reveal that effective talent management practices, when aligned with a supportive organizational culture, significantly enhance employee retention. Recruitment and Onboarding, career development, and employee engagement are identified as the most crucial practices. Additionally, a positive organizational culture that promotes inclusiveness, flexibility, and recognition fosters employee loyalty and reduces turnover. The study highlights the importance of continuous learning and development, flexible work arrangements, and a culture of recognition in retaining IT professionals. It also underscores the need for organizations to adapt to the evolving expectations of employees, particularly in terms of work-life balance and well-being. By integrating talent management with a strong organizational culture, IT companies can build a resilient workforce, minimize turnover costs, and achieve long-term success in a competitive market.